PEMBUDAYAAN PENGELOLAAN KEUANGAN BERBASIS AKUNTANSI BAGI PELAKU USAHA KECIL MENENGAH - Puspitaningtyas, Zarah (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
The problems faced by small and medium enterprises (SMEs), one of which is lack of ability in business finance management. Businesses often feel confined in their ability to apply accounting because they are not yet accustomed to practicing accounting in the management of their business finances. The solution of these problems, then the businesses needs to get training and assistance in a sustainable manner related to the financial management of accounting-based business, so as to manage their business finances effectively. The purpose of this study is to know the culture of accounting-based financial management for businesses Ã¢â‚¬Å“batikÃ¢â‚¬Â sector in Banyuwangi. The analysis was done by qualitative descriptive method, that is basing the result of observation and interview with informant. The results of the analysis concluded that accounting-based financial management can provide benefits for businesses to know the exact financial condition of the business, regulate and control the overall financial transactions that occur along the sustainability of its business. Therefore, businesses should familiarize (cultivate) to implement accounting-based financial management. The implication of the result of this study is expected to be composed of concepts related to the culture of accounting-based financial management for businesses actors, especially SMEs.